2006
DOI: 10.1007/s11557-005-0002-7
|View full text |Cite
|
Sign up to set email alerts
|

In vitro soil receptivity assays to egg-parasitic nematophagous fungi

Abstract: Soil application of nematophagous fungi for the biological control of plant-parasitic nematodes often fails, and in many cases it has been difficult to reisolate the agent delivered to the soil. A reason for these results could be the inability of the fungi to proliferate in soil. We used a soilmembrane technique to study the capacity of several isolates of the nematophagous fungi Pochonia chlamydosporia and Paecilomyces lilacinus to grow and establish in sterilized and nonsterilized sandy soils from SE Spain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 23 publications
1
17
0
3
Order By: Relevance
“…Selecting and testing isolates in the laboratory probably only served to reduce the number of isolates that needed to be tested in the greenhouse, because isolates that perform well in vitro may not be effective in soil (Kerry, 2001). All tested nematophagous fungi were inhibited when growing in nonsterilized soil, irrespective of the amount of nonsterilized soil (25-100%) which suggests that a lack of soil receptivity could be due to soil microbial activities (Monfort et al, 2006), therefore we used unsterile soil to achieve more accurate results. The chlamydospore is the preferred type of inoculum because it does not need an additional nutrient source (Wang et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Selecting and testing isolates in the laboratory probably only served to reduce the number of isolates that needed to be tested in the greenhouse, because isolates that perform well in vitro may not be effective in soil (Kerry, 2001). All tested nematophagous fungi were inhibited when growing in nonsterilized soil, irrespective of the amount of nonsterilized soil (25-100%) which suggests that a lack of soil receptivity could be due to soil microbial activities (Monfort et al, 2006), therefore we used unsterile soil to achieve more accurate results. The chlamydospore is the preferred type of inoculum because it does not need an additional nutrient source (Wang et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Addition of an energy base could increase competition from the residual microflora, which may reduce the survival and multiplication of Pochonia (Kok et al, 2001). In the other hand an energy source colonized by the fungus was considered essential for the establishment of inocula of hyphae and conidia applied to mineral soils (De Leij and Kerry, 1991;Monfort et al, 2006). Since most of the soil in Iran is mineral, barley bran was selected as energy source.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A reason for these results could be the inability of the fungi to proliferate in soil. Growth of all fungi tested (P. chlamydosporia and P. lilacinus) was inhibited in non-sterilised soil compared with sterilised treatments (Monford et al, 2006). Nematophagous activity of P. chlamydosporia in natural and autoclaved soil on tomato plants infested with M. javanica was evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Results indicated that a soil can be more receptive to its indigenous isolates than to non-indigenous iso-lates. Apparently, soil microbiota can determine the ability of nematophagous fungi to proliferate in soil (Monford et al, 2006). Perhaps in the future we will be able to integrate biological control with other control measures like moderately resistant rootstock on guava (Carneiro et al, 2007).…”
Section: Discussionmentioning
confidence: 99%